Modelamiento termodinámico de la precipitación de asfaltenos para el aseguramiento del flujo en un campo colombiano (2011)
In this paper is developed a thermodynamic modeling of asphaltene precipitation in order to predict the behavior of these in a fluid of a Colombian field this would be achieved by applying a multi-solid model, and a pseudo-characterization which treats the precipitated asphalten as a single pseudo-component in a solid state, who resides in a fluid whose phases are modeled by using a cubic EOS (equation of State). As a final product of this paper aims to provide a tool that allows to predict the behavior of precipitation of asphaltene and thus as a supplement in the decisionmaking process, to avoid future problems of production and minimize operational costs.